Experimental and theoretical study on the transformation of typical organic sulfur during hydrothermal carbonization of sludge. (15th January 2023) - Cheng, Shan; Huang, Jingchun; Luo, Rui; Tian, Hong; Yin, Yanshan; Qiao, Yu
Highlights: HTC of organic-S combined with DFT method are conducted to reveal S transformation. The S atom is the initial attacked position in organic-S molecule by nucleophile. H2 S/CH3 SH, as the major odorant, is mainly generated from aliphatic-S. The routes that aliphatic-S/aromatic-S changes to the SO4 2- /SO3 2- ion were proposed. Abstract: This study reports the migration and transformation of sulfur during the hydrothermal carbonization of sludge and two thermal unstable organic-S model compounds (aliphatic-S and aromatic-S) at 150 to 240 °C, focusing on the pathways based on the molecular level. The theoretical calculation indicates that the sulfur atom is the initial attacked position by nucleophile in the organic-S molecule, caused by its maximum contribution (i.e., 73.54 % for aliphatic-S) to the highest occupied molecular orbital (HOMO) and the minimum point of electrostatic potential (ESP, i.e., −103.68 kJ/mol for aliphatic-S). This leads to the nucleophilic addition reaction of aliphatic-S and aromatic-S, especially at 210 °C, along with the generation of sulfoxide-S and sulfone-S. Compared with aromatic-S, the aliphatic-S is more inclined to oxidation because of its higher HOMO contribution and lower ESP. Due to the low bond dissociation energy of CS of formed sulfoxide-S and sulfone-S, large of them (i.e., 47.51 % at 210 °C) transform to SO3 2- and SO4 2- ions via desulfurization and oxidation reactions, resulting in a low sulfur content in hydrochar. Also, the sulfoxide-S derived from aliphatic-S is more likely to decompose than other intermediates, together with the aliphatic-S, released as sulfur-containing odorants (especially for H2 S, CH3 SH and SO2 ). These findings indicate that fixing the aliphatic-S is an effectively method to control the emission of odorants.